Pine weevil (Hylobius abietis) preferences among species of conifer seedlings planted on clear-cuts in central Europe - Dvořáková, Barbora; Holuša, Jaroslav; Horák, Jakub; Hradecký, Jaromír; Bledý, Michal; Zelenka, Martin (Frontiers in Forests and Global Change, 2024)
Introduction As a result of climate change and bark beetle outbreaks in forests, extensive salvage, and sanitary cutting have been undertaken in Europe, resulting in many clear-cuts with coarse stumps. The populations of pine weevils (Hylobius abietis and Hylobius pinastri) are steadily increasing. A high abundance of pine weevils feeding on seedlings typically results in significant economic losses and prolongs the forest establishment period. However, information on these species spatial distribution and habitat selection patterns, necessary for assessing their harmfulness and subsequently accurately estimating their threat to reforested areas, is lacking. To determine which factors influence spatial selection patterns and seedling type preference, this study investigated which clear-cut factors increase pine weevil abundance and which seedling types (species and age) are the most preferred. Methods The experiment was carried out on 20 clear-cuts in the central Czech Republic. We evaluated soil moisture level, average stump distance and diameter, proportion of other conifers, and whether the stumps were mulched. We detected the abundance of pine weevils using pitfall traps. We determined the feeding scar intensity on the first 10 cm of seedling stems on commonly used seedlings for reforestation in central Europe: 1-year-old Scots pine (Pinus sylvestris), European larch (Larix decidua), and 3-year-old Norway spruce (Picea abies), with 1,200 seedlings in total. The individual seedling types alternated in rows. The results were evaluated using generalized linear mixed-effect models (GLMMs). As dependent variables we used total numbers of H. abietis and H. pinastri. The soil moisture level, mulching, proportion of other conifers, average stump diameter, and distance were considered independent variables. Results We found that Norway spruce was the least attractive to pine weevils. We found a higher abundance of H. abietis females in moist clear-cuts, confirming that dry clear-cuts are less suitable for oviposition. Conclusion According to our findings, if foresters want to plant coniferous seedlings, it seems that planting older spruce is a better option than planting larch and pine. These findings provide valuable insights for forest management and reforestation strategies, equipping foresters with the knowledge to mitigate the threat of pine weevils and ensure successful forest establishment.